2012
DOI: 10.7251/ssh1202182i
|View full text |Cite
|
Sign up to set email alerts
|

Preferencije učenika osnovnih škola za uvođenje izbornog sporta

Abstract: Cilj ovog rada je da da se ustanovi koji sportovi su najpopularniji kod učenika osnovnih škola na teritoriji Beograda, kako bi se ustanovilo koje bi sportove bilo poželjno uvesti kao izborni čas u nastavi fizičkog vaspitanja. Uzorkom je bilo obuhvaćeno 3 090 učenika. Najpopularniji sportovi su bili košarka, plivanje, odbojka a najmanje popularni akrobatika, orijentiring, ritmička gimnastika. Pokazalo se da postoji statistički značajna razlika u odnosu na pol (dječaci su u većoj mjeri priželjkivali uvođenje koš… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 1 publication
2
7
1
1
Order By: Relevance
“…Male teachers perceive this activity as appropriate for female students (Waddington, Malcolm, & Cobb, 1998), and so do the students themselves (Hill & Cleven, 2005). In support of this view, research also reports that dance, as an optional sport, is much more prevalent in girls and better students (Ilić, Radojević, Marković, & Višnjić, 2012). Also, it has been observed that dancing is one of the most common extracurricular physical activity for students who are exempt (increasingly) from compulsory physical education in primary and secondary schools.…”
Section: Introductionmentioning
confidence: 88%
“…Male teachers perceive this activity as appropriate for female students (Waddington, Malcolm, & Cobb, 1998), and so do the students themselves (Hill & Cleven, 2005). In support of this view, research also reports that dance, as an optional sport, is much more prevalent in girls and better students (Ilić, Radojević, Marković, & Višnjić, 2012). Also, it has been observed that dancing is one of the most common extracurricular physical activity for students who are exempt (increasingly) from compulsory physical education in primary and secondary schools.…”
Section: Introductionmentioning
confidence: 88%
“…mogu doprinijeti, škerbićevski rečeno, »ozanimljivanju« i »oprivlačenju« nastavnog procesa (Škerbić, 2010). Ilić (2016) smatra kako zanemarivanje popularne kulture u školi vodi ka samoisključivanju škole iz zajednice i iznevjeravanju njene osnovne uloge -oblikovanju obrazaca i vrijednosti u zajednici. Cerić (2013Cerić ( , 2019 razmatra mogućnosti primjene stripa u nastavi i nudi teorijska polazišta za sistematsko znanstveno proučavanje stripa kao svojevrsnog nastavnog medija te se zalaže za etabliranje nove nastavne metode u nastavi koju je nazvao 'stripovnom metodom' u nastavi.…”
Section: Strip Kao Nastavni Medij I Stripovna Metoda U Nastaviunclassified
“…The system of dependent variables includes the following selection of sports: athletics, aerobics, aikido, acrobatics, badminton, cycling, judo, fitness, soccer, gymnastics, karate, basketball, volleyball, orienteering, swimming, rhythmic gymnas-tics, handball, wrestling, synchronised swimming, skiing, sports dancing, table tennis, archery, taekwondo, tennis, water polo, and rowing. The list of sports was based on previous, select research (Radojević et al, 2011;Ilić et al 2012;Ilić, 2013).…”
Section: Questionnairementioning
confidence: 99%
“…In Serbia, there are very few studies (Ilić, 2013) that focus on parental attitudes towards physical education classes, and more studies are focused on the children's participation in them (Krsmanović, 1996;Đorđić & Tumin, 2008;Milanović & Radisavljević -Janić, 2011;Radojević et al, 2011;Šekeljić & Stamatović, 2011;Ilić et al, 2012;Šekeljić et al, 2012;Višnjić & Sretenović, 2014). Interestingly, no studies in Serbia focus on the interaction of the interests of parents and children, while some studies have tried to investigate the significance of the role of active parental involvement in their children's elementary education process (Radojlović et al, 2015).…”
Section: Introductionmentioning
confidence: 99%